2021
DOI: 10.1002/1878-0261.13095
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy‐induced increase in Th17 cell frequency in cervical cancer patients is associated with therapy resistance and early relapse

Abstract: Cervical cancer therapy is still a major clinical challenge, as patients substantially differ in their response to standard treatments, including chemoradiotherapy (CRT). During cervical carcinogenesis, T-helper (Th)-17 cells accumulate in the peripheral blood and tumor tissues of cancer patients and are associated with poor prognosis. In this prospective study, we find increased Th17 frequencies in the blood of patients after chemoradiotherapy and a posttherapeutic ratio of Th17/CD4 + T cells  8% was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…In line with previous studies describing Th17 cells as long living effector cells with high proliferative capacity and apoptosis‐resistant phenotype toward different cell death inducers, such as the chemotherapeutic drug cisplatin, 19 Fas‐mediated cell death in murine Th17 cells 34 or chemoradiotherapy in cervical cancer patients, 21 monitoring of vulvar cancer patients during therapy from this study revealed a decrease in CD4 + T cells in the patients' blood, but a significant increase in Th17 frequencies and absolute numbers after aRT in comparison to patients treated with surgery alone. Besides Th17 cells, frequencies of Tc17 cells but not γδT17 cells were also increased after aRT while frequencies of Th2 and Tregs were comparable to the surgery cohort.…”
Section: Discussionsupporting
confidence: 83%
“…In line with previous studies describing Th17 cells as long living effector cells with high proliferative capacity and apoptosis‐resistant phenotype toward different cell death inducers, such as the chemotherapeutic drug cisplatin, 19 Fas‐mediated cell death in murine Th17 cells 34 or chemoradiotherapy in cervical cancer patients, 21 monitoring of vulvar cancer patients during therapy from this study revealed a decrease in CD4 + T cells in the patients' blood, but a significant increase in Th17 frequencies and absolute numbers after aRT in comparison to patients treated with surgery alone. Besides Th17 cells, frequencies of Tc17 cells but not γδT17 cells were also increased after aRT while frequencies of Th2 and Tregs were comparable to the surgery cohort.…”
Section: Discussionsupporting
confidence: 83%
“…Th17 cells are a subset of CD4+ T cells, secrete different cytokines, and play a role in chronic inflammation, autoimmune diseases like Multiple Sclerosis, and cancer [35,36]. Concerning cancer, there are data showing that Th17 cells can promote tumorigenesis and progression depending on the tumor entity [37][38][39]. Th17 cells can contribute to angiogenesis and tumor vascularization [40].…”
Section: Discussionmentioning
confidence: 99%
“…Theobald et al reported that chemoradiotherapy increased Th17 cells in the peripheral blood of cervical cancer patients and that higher Th17 cells after therapy were associated with recurrent cervical cancer [39].…”
Section: Discussionmentioning
confidence: 99%
“…The constitution of the HPV-associated tumor microenvironment is critical for tumor development, therapy responses and affects progression of disease (5,6). Invasive cervical cancers are often associated with strong inflammatory infiltrates in the stroma (7).…”
Section: Introductionmentioning
confidence: 99%
“…Th17 cells represent an IL-17-expressing subgroup of Th cells (12). They increase in the blood of cervical cancer patients (13), infiltrate cervical cancer tissues (11) and exhibit pro-inflammatory as well as tumor-promoting properties in different cancer types (6,14,15). During cervical carcinogenesis, we previously demonstrated that cervical cancer cells actively contributed to the infiltration (11) and expansion (10) of Th17 cells in tumor tissues and their presence in situ correlated with advanced tumor stage, lymph node metastases (10,11), reduced responsiveness of patients toward CRT (6) and retrospectively, with cervical cancer recurrence (6,10).…”
Section: Introductionmentioning
confidence: 99%